Comparison of diagnostic accuracy of APRI and Transient Elastography for prediction of esophageal variceal bleed in liver cirrhosis - Kumar, Shailesh; Kumar, Vinay; Giri, Richa; Gautam, S. K. (International Journal of Research in Medical Sciences, 2023)
Background: Liver Cirrhosis is the end-stage for chronic liver disease. Repeated course of endoscopy is recommended, as this intervention is expensive and often poorly accepted by patients, there is a need for non-invasive methods to predicts the progression of portal hypertension as well as the presence and size of esophageal varices. This study was aimed to assess the APRI and Transient Elastography for predicting esophageal variceal bleed in cirrhotic patients. Objectives of the study were to study Diagnostic accuracy of APRI for Prediction of esophageal variceal bleed in liver cirrhosis, diagnostic accuracy of Transient Elastography for Prediction of esophageal variceal bleed in liver cirrhosis, comparison of diagnostic accuracy of APRI and Transient Elastography for Prediction of esophageal variceal bleed in liver cirrhosis. Methods: It was a Single centre, observational study in 35 patients of chronic liver disease. Patients were included in the study after fulfilling inclusion and exclusion criteria. CBC, LFT, KFT, SE, viral marker, USG whole abdomen, UGIE, Transient Elastography was done. APRI was calculated for every patient. Results: The APRI and Transient Elastography showed moderate diagnostic accuracy in predicting the presence of esophageal variceal bleed. Transient Elastography performed better for prediction of esophageal variceal bleed. Conclusions: The APRI and Transient Elastography showed moderate diagnostic accuracy in predicting the presence of esophageal variceal bleed. They help in starting prophylactic therapy earlier to prevent the bleeding and other complications of varices. These non-invasive parameters can also play an effective role in conjunction with endoscopy in predicting the presence of esophageal varices.